Acoustic Actuation of Integrin-Bound Microbubbles for Mechanical Phenotyping during Differentiation and Morphogenesis of Human Embryonic Stem Cells - Fan, Zhenzhen (Small, 2018)
Early human embryogenesis is a dynamic developmental process, involving continuous and concomitant changes in gene expression, structural reorganization, and cellular mechanics. However, the lack of investigation methods has limited the understanding of how cellular mechanical properties change during early human embryogenesis. In this study, ultrasound actuation of functionalized microbubbles targeted to integrin (acoustic tweezing cytometry, ATC) is employed for in situ measurement of cell stiffness during human embryonic stem cell (hESC) differentiation and morphogenesis. Cell stiffness, which is regulated by cytoskeleton structure, remains unchanged in undifferentiated hESCs, but significantly increases during neural differentiation. Further, using the recently established in vitro 3D embryogenesis models, ATC measurements reveal that cells continue to stiffen while maintaining pluripotency during epiblast cyst formation. In contrast, during amniotic cyst formation, cells first become stiffer during luminal cavity formation, but softens significantly when cells differentiate to form amniotic cysts. These results suggest that cell stiffness changes not only due to 3D spatial organization, but also with cell fate change. ATC therefore provides a versatile platform for in situ measurement of cellular mechanical property, and cell stiffness may be used as a mechanical biomarker for cell lineage diversification and cell fate specification during embryogenesis.